A survey of the experiences of delivering physiotherapy services through telerehabilitation during the COVID-19 pandemic - Peng, Tzu-Hsuan; Eng, Janice J.; Harris, Anne; Le Cornu Levett, Catherine; Yao, Jennifer; Schneeberg, Amy; Pollock, Courtney L. (Frontiers in Rehabilitation Sciences, 2024)
IntroductionPhysiotherapy services have been typically provided in-person since the profession usually involves a therapist providing hands-on assessment and treatments. The COVID-19 pandemic provided an opportunity to study physiotherapists’ adaptation to telerehabilitation (phone or videoconference).ObjectiveThis study aimed: (1) to explore how physiotherapists adapted to the transition to delivering telerehabilitation, (2) to assess physiotherapists’ perceptions of implementing telerehabilitation, and (3) to identify the challenges and facilitators of delivering telerehabilitation.MethodsThis study used an online survey distributed to physiotherapists within a large Canadian health authority. Closed-ended questions were analyzed with descriptive statistics.ResultsSeventy-five physiotherapists responded and data were collected. Compared prior to the pandemic to time during the pandemic, the use of a phone for delivering physiotherapy increased from 24.0% to 73.3% of physiotherapists while videoconference increased from 5.3% to 77.3%. Overall, the physiotherapists found videoconference to be a more effective delivery method than phone. Less than half felt that they could use videoconference to effectively treat pain (49.3%), upper extremity function (40.0%) or strength/range of motion (48.0%). Only 29.3% felt that they could effectively treat walking balance or mobility by videoconference. Technical barriers were identified with client comfort with the equipment reported by 90.7% of physiotherapists and positioning of the webcam by 76.0% of physiotherapists. A large proportion of physiotherapists agreed that they would continue the practice of telerehabilitation via phone (54.7%) and videoconference (68.0%).ConclusionThe pandemic resulted in a dramatic shift to telerehabilitation for a profession that typically provides hands-on assessments and treatments. While there was increased uptake of telerehabilitation, many physiotherapists questioned their effectiveness using telerehabilitation to undertake activities that traditionally involve manual treatments or hands-on guidance/supervision. However, physiotherapists were committed to continuing telerehabilitation to meet patients’ needs after the pandemic.